BAHAN AJAR BAHASA JAWA DI SMA BERBASIS NILAI-NILAI KEPRIBADIAN DAN PENDIDIKAN DALAM NASKAH KETOPRAK REMBULAN WUNGU KARYA BONDAN NUSANTARA: SEBUAH STUDI PSIKOLOGI SASTRA - Kristiaji, Yohanes; Sumarwati, Sumarwati; Kurwidaria, Favorita (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2018)
This research is aimed to describe: (1) The dynamics of personality in the Rembulan Wungu ketoprakscript by Bondan Nusantara; (2) The value of education in Rembulan Wungu ketoprakscript by Bondan Nusantara; and (3) The relevance of Rembulan Wungu ketoprakscript by Bondan Nusantara towards the teaching material of exposition text in Senior High School grade XI. This research is a descriptive qualitative research which used literature psychological approach. The sample was taken using purposive sampling technique. The data obtained from the Rembulan Wungu ketoprakscript by Bondan Nusantara, interviews with authors, literary experts especially ketoprak, people who are competent in psychology, Javanese language teachers, and students. Validity of data obtained through triangulation of theories, is doing the same topic research then researchers compare the documents or theory related to the object of the research. Data analysis technique used is flow analysis which includes three components, namely: data reduction, data presentation, and conclusion. The results of this research are: (1) The personality dynamics of characters in the Rembulan Wungu ketoprakscript by Bondan Nusantara are: (a) instinct, and (b) anxiety, The education values contained in the Rembulan Wungu ketoprakscript are religious, moral, social , and culture, from those four values social values are the most dominant values; and (3) The relevance of the Rembulan Wungu ketoprakscript by Bondan Nusantara enables and can be used as teaching material for exposition of Javanese performing arts in Senior High School, this can be seen in terms of content, language, and the education values contained in it.